The effect of nano POFA and nano eggshell powder to hardened concrete propeties - Saleh Salem, Mohammed Hussein (2019)
Malaysia is one of the main crude palm oil producer and exporter in the world. Meanwhile, a million tonnes of agro wastes such as palm oil fuel ash (POFA) and eggshell (ESP) is being produced every year and it causes a problem in disposing of POFA and ESP. However, POFA and ESP have the high potential to be used as recycling construction materials in the production of concrete as it contains a high content of silica and calcium which possesses pozzolanic behaviour. For strength activity index of POFA and ES. Pozzolanic materials in concrete works are increasing, and are expected to continuously increase in the years ahead because of technological advancement and the desire for sustainable development. Concrete containing raw material is introduced to reduce the cost of the construction project by reducing the use of materials and formworks. Nano palm oil fuel ash and Nano eggshell powder has been treated and can be used as a partial replacement for cement in concrete due to its pozzolanic effect. The main purposes of this study are to investigate the effect of Nano POFA on concrete properties replacement as cement also to investigate the effect of Nano POFA with NESP on concrete properties replacement as cement improving the strength of concrete. There are six mixtures of concrete were prepared such as 0% of NPOFA and NESP as a control sample, 10%, 20%, 30% as NPOFA replacements and 2.5%, 5% as NESP replacements of cement. All the mix of fresh concrete specimen were casted into the cube (100x100x100). All specimens were tested to determine the compressive strength, UPV, Crbonation and Water absorption of concrete. All Specimens containing NPOFA and NESP were prepared at constant water-cement ratios of 0.5 with superplasticizer content of 1% with cement. The water absorption, UPV and compressive strength has been determined by the laboratory result where 20% of Nano POFA with 0% of Nano ESP replacement has the lowest water absorb, highest velocity of UPV and compressive strength compare to others so 20% of Nano POFA replacement is the optimum percentage as partial cement replacement. This optimum percentage conclude that the mix design is economical and friendly environmental to construction industry. The Study discovered that the compressive strength increased with NPOFA and NESP replacement up to 30% and 5% consequently the general optimum strength for all variable hardening tests was found at 30% of NPOFA and 5% of NESP replacement. In this study the objectives of this project is achieved because this project success to demonstrate Nano POFA and Nano ESP being a waste material, can be a good pozzolanic material on account of its higher silica and calcium content especially when its subjected to further treatment.